Conducta obstétrica en multipara de 37 años de edad con embarazo de 7 semanas ectópico ovárico - Arias Veloz, María Del Cisne (2021)
Ectopic pregnancy is the nesting and abnormal development of the fertilized egg outside the endometrial cavity, this is outside the uterus, so it is considered a potentially serious health problem, due to the negative consequences it causes in the woman's body that suffers from it, if it is not diagnosed in time, they can become quite serious and even lead to maternal death. Multiple risk conditions can be the cause of ectopic pregnancies. The most important are intrauterine device use, smoking, previous ectopic pregnancies, tubal surgical procedures, age, intercourse before age 18, and promiscuity. The general objective of the clinical case study is to determine the complications of ectopic pregnancy in a 37-year-old multiparous, through observation and data collection, a patient with said pathology was chosen, using the Diagnostic methodology, the Physical examination evaluation verifying his symptoms, evaluating the results of laboratory tests and pelvic and obstetric ultrasound, which projects a differential diagnosis in which surgical treatment was carried out.